Inferences with Ignorance: Logics of Questions - Peliš, Michal (Karolinum, 2016)
Inferences with Ignorance focuses on two formal logic systems that employ the type of inferences in which questions are used in addition to statements. Not merely capturing questions as part of a logical apparatus, Michal Peliš also emphasizes the role of question-asking in communication. The book presents options for formalizing questions using sets of "direct answers," demonstrates where questions are used in inferences, and explores asking questions and seeking answers as important components of everyday communication, proposing ways of using questions within a formal system that can capture a change in knowledge during this simple communication.
Keywords: Ostatní